Optical glass, glass preform, optical element and optical instrument

By reasonably preparing the components of P2O5, Nb2O5, TiO2, BaO and Na2O in optical glass, the problem of harmful PbO in existing high refractive index and high dispersion optical glass is solved, and a high-performance, environmentally friendly and lightweight optical glass design is achieved.

CN119569334APending Publication Date: 2025-03-07CDGM OPTICAL GLASS
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202311149924.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-07
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The existing high refractive index and high dispersion optical glass contain PbO that is harmful to the environment, and the glass density is high, which is not conducive to the lightweight requirement of optical glass.

Method used

Optical glass design with components containing P2O5:20-35%, Nb2O5:37-55%, TiO2:1-12%, BaO:4-19%, and Na2O:0.5-14%, avoid using PbO, and optimize the refractive index, dispersion and density of the glass through a reasonable component ratio.

Benefits of technology

It achieves high refractive index and high dispersion performance without PbO, meets environmental protection requirements, and reduces the density of glass, making it suitable for the use of high-performance optical instruments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004436494440000161
    Figure BDA0004436494440000161
  • Figure BDA0004436494440000162
    Figure BDA0004436494440000162
  • Figure BDA0004436494440000181
    Figure BDA0004436494440000181
Patent Text Reader

Abstract

The invention provides optical glass, which comprises the following components in percentage by weight: 20 to 35 percent of P2O5; nb2O5: 37% to 55%; 1 to 12 percent of TiO2; 4% to 19% of BaO; and 0.5 to 14 percent of Na2O. Through reasonable component design, the optical glass provided by the invention does not contain components harmful to the environment, such as PbO, has high refraction and high dispersion performance, and meets the use of high-performance optical instruments.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an optical glass, in particular to an optical glass with a refractive index of 1.82-1.89 and an Abbe number of 18-26, and a glass preform, an optical element and an optical instrument made of the optical glass. Background Art

[0002] In recent years, the digitization of optical instruments or the high definition of images and videos are developing at a high speed. In particular, the high definition of images and videos is very prominent in optical instruments such as digital cameras, video cameras, and projectors. At the same time, in the optical systems contained in these optical instruments, the number of optical elements such as lenses or prisms is reduced to achieve lightweight and miniaturization. Under the same radius of curvature, the higher the refractive index of the glass, the larger the imaging field of view, which is conducive to reducing the number of optical elements in the optical instrument. With the development trend of miniaturization of optical instruments, the demand for high refractive index and high dispersion optical glass with a refractive index of 1.82 to 1.89 and an Abbe number of 18 to 26 is becoming more and more obvious.

[0003] Chinese patents CN1186279C and CN1229293C respectively disclose a high refractive index and high dispersion optical glass, each of which contains a large amount of PbO, which is harmful to the environment, and the density of the glass is high, which is not conducive to the requirement of lightweight optical glass. Chinese patents CN102471130A, CN101932532A, CN101289275A, etc. respectively disclose a high refractive index and high dispersion optical glass, each of which contains a large amount of SiO 2 , its solubility needs to be improved. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide an optical glass with a refractive index of 1.82-1.89 and an Abbe number of 18-26, which meets environmental protection requirements.

[0005] The technical solution adopted by the present invention to solve the technical problem is:

[0006] Optical glass, its components expressed in weight percentage, contains: P 2 O 5 :20~35%; Nb 2 O 5 :37~55%;TiO 2 : 1~12%; BaO: 4~19%; Na 2 O: 0.5~14%.

[0007] Furthermore, the optical glass, expressed in weight percentage, further contains: CaO: 0-8%; and / or MgO: 0-5%; and / or SrO: 0-8%; and / or ZnO: 0-5%; and / or Li 2 O: 0-5%; and / or K 2 O: 0-5%; and / or Ln 2 O 3 :0~5%;and / or SiO 2 :0~5%;and / or B 2 O 3 : 0-5%; and / or Al 2 O 3 : 0-3%; and / or WO 3 :0~3%;and / or ZrO 2 :0~5%; and / or Bi 2 O 3 : 0-3%; and / or clarifier: 0-1%, the Ln 2 O 3 For La 2 O 3 , Gd 2 O 3 , Y 2 O 3 , Yb 2 O 3 、Lu 2 O 3 One or more of the following, the clarifier is Sb 2 O 3 SnO 2 、CeO 2 One or more of .

[0008] Optical glass, its components are expressed in weight percentage, consisting of P 2 O 5 :20~35%; Nb 2 O 5 :37~55%;TiO 2 : 1~12%; BaO: 4~19%; Na 2 O: 0.5~14%; CaO: 0~8%; MgO: 0~5%; SrO: 0~8%; ZnO: 0~5%; Li 2 O: 0~5%; K 2 O: 0~5%; Ln 2 O 3 :0~5%;SiO 2 :0~5%; B 2 O 3 :0~5%;Al 2 O 3:0~3%;WO 3 :0~3%;ZrO 2 :0~5%;Bi 2 O 3 :0~3%; clarifier: 0~1% composition, the Ln 2 O 3 For La 2 O 3 , Gd 2 O 3 , Y 2 O 3 , Yb 2 O 3 、Lu 2 O 3 One or more of the following, the clarifier is Sb 2 O 3 SnO 2 、CeO 2 One or more of .

[0009] Furthermore, the optical glass has components expressed in weight percentage, wherein:

[0010] (ZnO+Li 2 O+K 2 O+WO 3 +B 2 O 3 +Bi 2 O 3 ) / SrO is 2.0 or less, preferably

[0011] (ZnO+Li 2 O+K 2 O+WO 3 +B 2 O 3 +Bi 2 O 3 ) / SrO is 1.5 or less, and more preferably (ZnO+Li 2 O+K 2 O+WO 3 +B 2 O 3 +Bi 2 O 3 ) / SrO is less than 1.0, and more preferably (ZnO+Li 2 O+K 2 O+WO 3 +B 2 O 3 +Bi 2 O 3 ) / SrO is less than 0.5.

[0012] Furthermore, the optical glass, wherein: (Li 2 O+B 2 O 3 +Bi 2 O 3 ) / TiO 2 is 1.0 or less, preferably (Li 2 O+B 2 O 3 +Bi 2 O 3 ) / TiO 2 is 0.8 or less, more preferably (Li 2 O+B 2 O 3 +Bi 2 O 3 ) / TiO 2 is 0.5 or less, and more preferably (Li 2 O+B 2 O 3 +Bi 2 O 3 ) / TiO 2 Is less than 0.2.

[0013] Furthermore, the optical glass has components expressed in weight percentage, wherein: SrO / TiO 2 0.01 to 5.0, preferably SrO / TiO 2 0.01 to 2.0, more preferably SrO / TiO 2 is 0.05 to 1.0, and SrO / TiO is more preferred 2 It is 0.1~0.7.

[0014] Furthermore, the optical glass has components expressed in weight percentage, wherein: BaO / (Na 2 O+K 2 O+TiO 2 ) is 0.4 to 5.0, preferably BaO / (Na 2 O+K 2 O+TiO 2 ) is 0.5 to 3.0, more preferably BaO / (Na 2 O+K 2 O+TiO 2 ) is 0.6 to 2.5, and BaO / (Na 2 O+K 2 O+TiO 2 ) is 0.7~1.5.

[0015] Furthermore, the optical glass, its components are expressed in weight percentage, wherein: Nb 2O 5 / P 2 O 5 1.3 to 2.7, preferably Nb 2 O 5 / P 2 O 5 1.4 to 2.5, more preferably Nb 2 O 5 / P 2 O 5 is 1.5 to 2.2, and Nb is more preferably 2 O 5 / P 2 O 5 It is 1.6~2.0.

[0016] Furthermore, the optical glass has components expressed in weight percentage, wherein:

[0017] (SiO 2 +CaO+ZnO) / SrO is 0.3 to 8.0, preferably (SiO 2 +CaO+ZnO) / SrO is 0.5 to 5.0, and more preferably (SiO 2 +CaO+ZnO) / SrO is 0.6 to 3.0, and more preferably (SiO 2 +CaO+ZnO) / SrO is 0.7~2.0.

[0018] Furthermore, the optical glass has components expressed in weight percentage, wherein:

[0019] (WO 3 +ZnO+K 2 O+CaO+MgO) / TiO 2 2.0 or less, preferably (WO 3 +ZnO+K 2 O+CaO+MgO) / TiO 2 0.05 to 1.5, more preferably (WO 3 +ZnO+K 2 O+CaO+MgO) / TiO 2 is 0.1 to 1.0, and more preferably (WO 3 +ZnO+K 2 O+CaO+MgO) / TiO 2 It is 0.2~0.8.

[0020] Furthermore, the optical glass has components expressed in weight percentage, wherein:

[0021] (WO 3 +K 2 O+TiO2 +B 2 O 3 ) / Nb 2 O 5 0.03 to 0.4, preferably (WO 3 +K 2 O+TiO 2 +B 2 O 3 ) / Nb 2 O 5 0.04 to 0.3, more preferably (WO 3 +K 2 O+TiO 2 +B 2 O 3 ) / Nb 2 O 5 is 0.05 to 0.25, more preferably (WO 3 +K 2 O+TiO 2 +B 2 O 3 ) / Nb 2 O 5 It is 0.06~0.15.

[0022] Furthermore, the optical glass, its components are expressed in weight percentage, wherein: Na 2 O / BaO is 0.05 to 2.0, preferably Na 2 O / BaO is 0.1 to 1.5, preferably Na 2 O / BaO is 0.2 to 1.0, and Na 2 O / BaO is 0.4~0.9.

[0023] Furthermore, the optical glass has its components expressed in weight percentage, wherein: BaO / P 2 O 5 0.15~0.9, preferably BaO / P 2 O 5 0.25 to 0.8, more preferably BaO / P 2 O 5 is 0.3 to 0.7, and BaO / P is more preferably 2 O 5 It is 0.35~0.6.

[0024] Furthermore, the optical glass has components expressed in weight percentage, wherein:

[0025] (Li 2 O+B 2 O 3 +TiO2 ) / BaO is 0.06 to 2.0, preferably (Li 2 O+B 2 O 3 +TiO 2 ) / BaO is 0.07 to 1.5, and more preferably (Li 2 O+B 2 O 3 +TiO 2 ) / BaO is 0.08 to 1.0, and more preferably (Li 2 O+B 2 O 3 +TiO 2 ) / BaO is 0.1~0.5.

[0026] Furthermore, the optical glass has components expressed in weight percentage, wherein: TiO 2 / CaO is 0.4 to 10.0, preferably TiO 2 / CaO is 0.8 to 8.0, and TiO is more preferred 2 / CaO is 1.0 to 6.0, and TiO is more preferred 2 / CaO is 1.2~5.0.

[0027] Furthermore, the optical glass is represented by weight percentage, wherein: 2 O 5 : 22-32%, preferably P 2 O 5 :25~30%;and / or Nb 2 O 5 : 41-52%, preferably Nb 2 O 5 : 43-50%; and / or TiO 2 : 2-10%, preferably TiO 2 : 3-7%; and / or BaO: 6-16.5%, preferably BaO: 10-15%; and / or Na 2 O: 2-12%, preferably Na 2 O: 5-10%; and / or CaO: greater than 0 but less than or equal to 6%, preferably CaO: 1-4%; and / or MgO: 0-3%, preferably MgO: 0-1%; and / or SrO: greater than 0 but less than or equal to 5%, preferably SrO: 0.5-3%; and / or ZnO: 0-3%, preferably ZnO: 0-1%; and / or Li 2 O: 0-3%, preferably Li 2 O: 0-1%; and / or K 2 O: 0-3%, preferably K 2 O: 0-1%; and / or Ln2 O 3 : 0-3%, preferably Ln 2 O 3 :0~1%;and / or SiO 2 : 0-3%, preferably SiO 2 :0~1%;and / or B 2 O 3 : 0-3%, preferably B 2 O 3 :0~1%;and / or Al 2 O 3 : 0-2%, preferably Al 2 O 3 : 0-1%; and / or WO 3 : 0-2%, preferably WO 3 :0~1%;and / or ZrO 2 : 0-2%, preferably ZrO 2 :0~1%; and / or Bi 2 O 3 : 0-2%, preferably Bi 2 O 3 : 0-1%; and / or clarifier: 0-0.5%, preferably clarifier: 0-0.1%, the Ln 2 O 3 For La 2 O 3 , Gd 2 O 3 , Y 2 O 3 , Yb 2 O 3 、Lu 2 O 3 One or more of the following, the clarifier is Sb 2 O 3 SnO 2 、CeO 2 One or more of .

[0028] Furthermore, the optical glass does not contain MgO; and / or does not contain ZnO; and / or does not contain Li 2 O; and / or does not contain K 2 O; and / or does not contain Ln 2 O 3 ; and / or does not contain B 2 O 3 ; and / or does not contain Al 2 O 3 ; and / or does not contain WO 3 ; and / or does not contain ZrO 2 ; and / or does not contain Bi2 O 3 ; and / or does not contain a clarifier, the Ln 2 O 3 For La 2 O 3 , Gd 2 O 3 , Y 2 O 3 , Yb 2 O 3 、Lu 2 O 3 One or more of the following, the clarifier is Sb 2 O 3 SnO 2 、CeO 2 One or more of .

[0029] Furthermore, the refractive index n of the optical glass is d 1.82 to 1.89, preferably 1.83 to 1.88, more preferably 1.84 to 1.87; Abbe number ν d It is 18-26, preferably 20-25, and more preferably 21-24.

[0030] Furthermore, the thermal expansion coefficient α of the optical glass is 100 / 300℃ 100×10 -7 / K or less, preferably 95×10 -7 / K or less, more preferably 90×10 -7 / K or less; and / or acid resistance stability D A 2 or more, preferably 1; and / or water resistance stability D W Two or more types, preferably one type; and / or relative partial dispersion P g,F 0.58 to 0.72, preferably 0.60 to 0.68, more preferably 0.62 to 0.65; and / or relative partial dispersion deviation value ΔP g,F is 0.08 or less, preferably 0.005 to 0.06, more preferably 0.01 to 0.04; and / or the transition temperature T g 670°C or less, preferably 660°C or less, more preferably 650°C or less; and / or abrasion degree F A 250 to 290, preferably 260 to 285, more preferably 265 to 280; and / or density ρ is 4.00 g / cm 3 Below, preferably 3.90g / cm 3 Below, more preferably 3.80g / cm 3 Below; and / or 70 430nm or less, preferably λ 70420nm or less, preferably λ 70 is below 410nm; and / or λ 5 400nm or less, preferably λ 5 390nm or less, preferably λ 5 380nm or less; and / or weather resistance CR is 2 or more, preferably 1; and / or Young's modulus E is 8000×10 7 Pa or more, preferably 8500×10 7 Pa or more, more preferably 9000×10 7 Pa or above; and / or the bubble degree is above grade A, preferably A 0 Grade A or above, preferably A 00 class.

[0031] The glass preform is made of the above optical glass.

[0032] The optical element is made of the above optical glass, or made of the above glass preform.

[0033] An optical instrument containing the above optical glass or the above optical element.

[0034] The beneficial effects of the present invention are: through reasonable component design, the optical glass of the present invention does not contain components harmful to the environment such as PbO, and at the same time has high refractive and high dispersion properties, meeting the use of high-performance optical instruments. DETAILED DESCRIPTION

[0035] The following will describe the embodiments of the optical glass of the present invention in detail, but the present invention is not limited to the following embodiments, and can be implemented by appropriate changes within the scope of the purpose of the present invention. In addition, although there are appropriate omissions of descriptions of the repeated descriptions, the gist of the invention will not be limited thereby, and in the following content, the optical glass of the present invention is sometimes referred to as glass.

[0036] [Optical glass]

[0037] The following is an explanation of the range of each component (ingredient) of the optical glass of the present invention. In the present invention, unless otherwise specified, the content and total content of each component are all expressed in weight percentage (wt%), that is, the content and total content of each component are expressed in weight percentage relative to the total amount of glass material converted into oxide composition. Here, the "composition converted into oxide" means that when the oxides, complex salts and hydroxides used as raw materials for the optical glass components of the present invention decompose and transform into oxides during melting, the total amount of the oxide material is taken as 100%.

[0038] Unless otherwise specified in specific circumstances, the numerical ranges listed in the present invention include upper and lower limits, "above" and "below" include endpoint values, and all integers and fractions included in the range, without being limited to the specific values ​​listed when the range is defined. "And / or" referred to herein is inclusive, for example, "A and / or B" means only A, or only B, or both A and B.

[0039] <Essential Components and Optional Components>

[0040] P 2 O 5 It is the network generator of the glass of the present invention. Compared with silicate glass, phosphate glass can be melted at a low temperature, which is beneficial to improve the light transmittance of the glass. 2 O 5 If the content of P is too high, it is difficult for the glass to obtain a higher refractive index. 2 O 5 The content of is 20 to 35%, preferably 22 to 32%, and more preferably 25 to 30%.

[0041] Nb 2 O 5 It is a high refractive and high dispersion component that can increase the refractive index and resistance to devitrification of glass, and has the effect of reducing the relative partial dispersion (P g,F ) and relative partial dispersion deviation (ΔP g,F ) in the present invention, by containing more than 37% Nb 2 O 5 In order to obtain the above effects, Nb is preferably 2 O 5 The lower limit of the content of Nb is 41%, and the more preferred lower limit is 43%. 2 O 5 If the content of Nb exceeds 55%, the thermal stability and chemical stability of the glass will decrease, and the light transmittance will decrease. 2 O 5 The upper limit of the content is 55%, preferably 52%, and more preferably 50%.

[0042] In some embodiments, Nb 2 O 5 The content of P 2 O 5 The ratio of Nb 2 O 5 / P 2 O 5 Controlling it within the range of 1.3 to 2.7 can improve the anti-crystallization performance and chemical stability of the glass, optimize the Young's modulus of the glass, and more easily obtain the desired P g,F Value and ΔP g,FTherefore, Nb is preferred 2 O 5 / P 2 O 5 1.3 to 2.7, more preferably Nb 2 O 5 / P 2 O 5 is 1.4 to 2.5, and Nb is more preferably 2 O 5 / P 2 O 5 is 1.5 to 2.2, and Nb is more preferably 2 O 5 / P 2 O 5 It is 1.6~2.0.

[0043] TiO 2 It has high refractive and high dispersion properties, can improve the chemical stability of glass, and adjust the relative partial dispersion of glass (P g,F ) and relative partial dispersion deviation (ΔP g,F ), if its content is too high, the devitrification resistance and light transmittance of the glass will decrease. 2 The content of is 1 to 12%, preferably 2 to 10%, and more preferably 3 to 7%.

[0044] BaO can improve the resistance to devitrification and hardness of glass, and reduce the temperature coefficient of refractive index and thermal expansion coefficient of glass. In the present invention, the above effects are obtained by containing more than 4% of BaO. Preferably, the content of BaO is more than 6%, and more preferably, the content of BaO is more than 10%. On the other hand, by making the content of BaO less than 19%, the reduction of chemical stability caused by excessive BaO content can be prevented. Therefore, the content of BaO is less than 19%, preferably, the content of BaO is less than 16.5%, and more preferably, the content of BaO is less than 15%.

[0045] In some embodiments, the content of BaO and P 2 O 5 The ratio of BaO / P 2 O 5 Controlling it within the range of 0.15 to 0.9 can improve the weather resistance and light transmittance of the glass and optimize the abrasiveness of the glass. 2 O 5 0.15 to 0.9, more preferably BaO / P 2 O 5 is 0.25 to 0.8, and BaO / P is more preferably 2 O 5 is 0.3 to 0.7, and BaO / P is more preferred 2O 5 It is 0.35~0.6.

[0046] CaO helps to adjust the optical constants of glass and improve the processing performance and weather resistance of glass, but when the content of CaO is too much, the anti-devitrification performance of glass will be deteriorated. Therefore, the content of CaO is 0 to 8%, preferably greater than 0 but less than or equal to 6%, and more preferably 1 to 4%.

[0047] In some embodiments, TiO 2 The ratio of TiO content to CaO content 2 Controlling TiO / CaO in the range of 0.4 to 10.0 is beneficial to reducing the thermal expansion coefficient of glass and optimizing the Young's modulus and abrasion resistance of glass. 2 / CaO is 0.4 to 10.0, and TiO is more preferred 2 / CaO is 0.8 to 8.0, and TiO is more preferred 2 / CaO is 1.0 to 6.0, and TiO is more preferred 2 / CaO is 1.2~5.0.

[0048] SrO can adjust the refractive index and dispersion of glass, but if the content is too high, the chemical stability of the glass will decrease and the cost of the glass will also increase. Therefore, the content of SrO is 0 to 8%, preferably greater than 0 but less than or equal to 5%, and more preferably 0.5 to 3%.

[0049] In some embodiments, the content of SrO is related to TiO 2 The ratio of SrO / TiO 2 Controlling it within the range of 0.01 to 5.0 is beneficial for the glass to have the desired P g,F Value and ΔP g,F value, while increasing the Young's modulus of the glass to prevent the decrease in light transmittance. Therefore, SrO / TiO is preferred. 2 0.01 to 5.0, more preferably SrO / TiO 2 is 0.01 to 2.0, and SrO / TiO is more preferred 2 is 0.05 to 1.0, and SrO / TiO is more preferred 2 It is 0.1~0.7.

[0050] MgO is beneficial for reducing the density and melting temperature of glass, but when the MgO content is too high, the refractive index of the glass is difficult to meet the design requirements, and the anti-devitrification performance and stability of the glass are reduced. Therefore, the content of MgO is 0-5%, preferably 0-3%, and more preferably 0-1%. In some embodiments, it is further preferred that MgO is not contained.

[0051] ZnO can reduce the glass transition temperature and the melting temperature, improve the chemical stability of the glass, and reduce the high temperature viscosity of the glass. If the ZnO content is too high, the anti-crystallization performance of the glass will deteriorate, and devitrification will easily occur due to the low viscosity. Therefore, the content of ZnO in the present invention is 0 to 5%, preferably 0 to 3%, and more preferably 0 to 1%. In some embodiments, it is further preferred that ZnO is not contained.

[0052] Li 2 O can improve the melting property of glass and reduce the transition temperature. If its content is too high, the refractive index of the glass will be difficult to meet the design requirements and the chemical stability of the glass will deteriorate. 2 The content of O is 0 to 5%, preferably 0 to 3%, and more preferably 0 to 1%. In some embodiments, it is further preferred that Li 2 O.

[0053] Na 2 O can improve the melting and forming properties of glass and optimize the light transmittance of glass. If its content is too high, it will be detrimental to the thermal expansion coefficient and chemical stability of glass. 2 The content of O is 0.5 to 14%, preferably 2 to 12%, and more preferably 5 to 10%.

[0054] In some embodiments, Na 2 The ratio of O content to BaO content is Na 2 O / BaO is controlled within the range of 0.05 to 2.0, which is beneficial to improving the bubble degree of the glass, optimizing the abrasiveness of the glass, and preventing the increase of the thermal expansion coefficient. 2 O / BaO is 0.05 to 2.0, preferably Na 2 O / BaO is 0.1 to 1.5, and Na 2 O / BaO is 0.2 to 1.0, and Na 2 O / BaO is 0.4~0.9.

[0055] K 2 O has the effect of improving the thermal stability and melting property of glass, but if its content is too high, the resistance to devitrification of glass will decrease. 2 The content of O is 0 to 5%, preferably 0 to 3%, and more preferably 0 to 1%. In some embodiments, it is further preferred that K is not contained. 2 O.

[0056] In some embodiments, the content of BaO and Na 2 O.K 2 O and TiO 2 Total content of Na 2 O+K 2O+TiO 2 The ratio between BaO / (Na 2 O+K 2 O+TiO 2 ) is controlled within the range of 0.4 to 5.0, the glass is easier to obtain the desired P g,F Value and ΔP g,F value to prevent the density of glass from increasing. Therefore, BaO / (Na 2 O+K 2 O+TiO 2 ) is 0.4 to 5.0, more preferably BaO / (Na 2 O+K 2 O+TiO 2 ) is 0.5 to 3.0. Further, control BaO / (Na 2 O+K 2 O+TiO 2 ) is within the range of 0.6 to 2.5, the abrasiveness and bubble degree of the glass can be further optimized. Therefore, BaO / (Na 2 O+K 2 O+TiO 2 ) is 0.6 to 2.5, and BaO / (Na 2 O+K 2 O+TiO 2 ) is 0.7~1.5.

[0057] Ln 2 O 3 (Ln 2 O 3 For La 2 O 3 , Gd 2 O 3 , Y 2 O 3 , Yb 2 O 3 、Lu 2 O 3 One or more of Ln is a component that increases the refractive index of the glass and is an optional component in the optical glass of the present invention. 2 O 3 The content of Ln is controlled to be less than 5%, which can prevent the devitrification resistance of the glass from decreasing. 2 O 3 The content of Ln is 0 to 5%, preferably 0 to 3%, and more preferably 0 to 1%. In some embodiments, it is further preferred that Ln is not contained. 2 O 3 .

[0058] Phosphate glass contains SiO 2, which can make the glass grid more compact and improve the chemical stability and mechanical strength of the glass. However, the phosphate glass grid has a strong 2 The compatibility is not strong. When SiO 2 When the content is too high, phase separation is likely to occur. 2 The content is 0 to 5%, preferably 0 to 3%, and more preferably 0 to 1%.

[0059] In some embodiments, SiO 2 The total content of SiO, CaO and ZnO 2 The ratio of the content of +CaO+ZnO to SrO (SiO 2 +CaO+ZnO) / SrO is controlled within the range of 0.3 to 8.0, which is beneficial to reducing the thermal expansion coefficient and density of the glass and optimizing the weather resistance of the glass. 2 +CaO+ZnO) / SrO is 0.3 to 8.0, and more preferably (SiO 2 +CaO+ZnO) / SrO is 0.5 to 5.0, and more preferably (SiO 2 +CaO+ZnO) / SrO is 0.6 to 3.0, and more preferably (SiO 2 +CaO+ZnO) / SrO is 0.7~2.0.

[0060] B 2 O 3 It has the effect of improving the thermal stability and melting property of glass, but when its content is high, the chemical stability and resistance to devitrification of glass decrease. 2 O 3 The content of B is 0 to 5%, preferably 0 to 3%, and more preferably 0 to 1%. In some embodiments, it is further preferred that B is not contained. 2 O 3 .

[0061] In some embodiments, Li 2 O.B 2 O 3 and TiO 2 Total content of Li 2 O+B 2 O 3 +TiO 2 The ratio of Li 2 O+B 2 O 3 +TiO 2 ) / BaO is controlled in the range of 0.06 to 2.0, which can improve the weather resistance of the glass, prevent the transition temperature from rising, and make it easier to obtain the desired P g,F Value and ΔPg,F Therefore, it is preferred that (Li 2 O+B 2 O 3 +TiO 2 ) / BaO is 0.06 to 2.0, and more preferably (Li 2 O+B 2 O 3 +TiO 2 ) / BaO is 0.07 to 1.5, and more preferably (Li 2 O+B 2 O 3 +TiO 2 ) / BaO is 0.08 to 1.0, and more preferably (Li 2 O+B 2 O 3 +TiO 2 ) / BaO is 0.1~0.5.

[0062] Al 2 O 3 It can improve the chemical stability of glass, but when its content exceeds 3%, the melting property and light transmittance of glass deteriorate. 2 O 3 The content of Al is 0-3%, preferably 0-2%, and more preferably 0-1%. In some embodiments, it is further preferred that Al is not contained. 2 O 3 .

[0063] WO 3 It is an optional component that can adjust the optical constants and devitrification resistance of glass, but when its content is high, the transmittance and anti-crystallization performance of glass decrease. 3 The content of WO is 0-3%, preferably 0-2%, and more preferably 0-1%. In some embodiments, it is further preferred that WO 3 .

[0064] In some embodiments, WO 3 , ZnO, K 2 The total content of O, CaO and MgO is WO 3 +ZnO+K 2 O+CaO+MgO and TiO 2 The ratio between the contents of 3 +ZnO+K 2 O+CaO+MgO) / TiO 2 Controlling it below 2.0 can reduce the glass transition temperature while increasing the bubble degree of the glass and optimizing the abrasiveness of the glass. 3 +ZnO+K 2O+CaO+MgO) / TiO 2 2.0 or less, more preferably (WO 3 +ZnO+K 2 O+CaO+MgO) / TiO 2 is 0.05 to 1.5, more preferably (WO 3 +ZnO+K 2 O+CaO+MgO) / TiO 2 is 0.1 to 1.0, and more preferably (WO 3 +ZnO+K 2 O+CaO+MgO) / TiO 2 It is 0.2~0.8.

[0065] In some embodiments, WO 3 , K 2 O、TiO 2 and B 2 O 3 Total content of WO 3 +K 2 O+TiO 2 +B 2 O 3 With Nb 2 O 5 The ratio between the contents of 3 +K 2 O+TiO 2 +B 2 O 3 ) / Nb 2 O 5 Controlling it within the range of 0.03 to 0.4 can reduce the thermal expansion coefficient of the glass and improve the light transmittance and chemical stability of the glass. 3 +K 2 O+TiO 2 +B 2 O 3 ) / Nb 2 O 5 0.03 to 0.4, more preferably (WO 3 +K 2 O+TiO 2 +B 2 O 3 ) / Nb 2 O 5 is 0.04 to 0.3, more preferably (WO 3 +K 2 O+TiO 2 +B 2 O 3 ) / Nb 2 O5 is 0.05 to 0.25, and more preferably (WO 3 +K 2 O+TiO 2 +B 2 O 3 ) / Nb 2 O 5 It is 0.06~0.15.

[0066] Appropriate amount of ZrO 2 It can increase the mechanical strength and hardness of glass, improve the anti-crystallization performance of glass, and adjust the P g,F Value and ΔP g,F But ZrO 2 It is difficult to melt in phosphate glass, and too much of it will lead to difficulty in chemical synthesis. 2 The content of ZrO is 0 to 3%, preferably 0 to 2%, and more preferably 0 to 1%. In some embodiments, it is further preferred that ZrO is not contained. 2 .

[0067] Bi 2 O 3 The refractive index of glass can be increased, but Bi 2 O 3 The density of Bi is large, which is not conducive to the lightweight design of glass. 2 O 3 The content of Bi is 0 to 3%, preferably 0 to 2%, and more preferably 0 to 1%. In some embodiments, it is further preferred that Bi is not contained. 2 O 3 .

[0068] In some embodiments, ZnO, Li 2 O.K 2 O.WO 3 , B 2 O 3 and Bi 2 O 3 Total content of ZnO+Li 2 O+K 2 O+WO 3 +B 2 O 3 +Bi 2 O 3 The ratio between the content of ZnO and SrO (ZnO+Li 2 O+K 2 O+WO 3 +B 2 O 3 +Bi 2 O 3) / SrO is controlled below 2.0, which can make the glass have a lower thermal expansion coefficient while increasing the bubble degree of the glass, optimizing the Young's modulus and preventing the decrease of light transmittance. Therefore, (ZnO+Li 2 O+K 2 O+WO 3 +B 2 O 3 +Bi 2 O 3 ) / SrO is 2.0 or less, and more preferably (ZnO+Li 2 O+K 2 O+WO 3 +B 2 O 3 +Bi 2 O 3 ) / SrO is 1.5 or less, and more preferably (ZnO+Li 2 O+K 2 O+WO 3 +B 2 O 3 +Bi 2 O 3 ) / SrO is less than 1.0, and more preferably (ZnO+Li 2 O+K 2 O+WO 3 +B 2 O 3 +Bi 2 O 3 ) / SrO is less than 0.5.

[0069] In some embodiments, Li 2 O.B 2 O 3 and Bi 2 O 3 Total content of Li 2 O+B 2 O 3 +Bi 2 O 3 With TiO 2 The ratio between the contents of 2 O+B 2 O 3 +Bi 2 O 3 ) / TiO 2 When the P value is controlled below 1.0, the glass has a lower transition temperature, which is beneficial to reduce the density of the glass, optimize the chemical stability of the glass, and it is easier to achieve the desired P value. g,F Value and ΔP g,F Therefore, it is preferred that (Li 2 O+B2 O 3 +Bi 2 O 3 ) / TiO 2 is 1.0 or less, more preferably (Li 2 O+B 2 O 3 +Bi 2 O 3 ) / TiO 2 is 0.8 or less, and more preferably (Li 2 O+B 2 O 3 +Bi 2 O 3 ) / TiO 2 is 0.5 or less, and more preferably (Li 2 O+B 2 O 3 +Bi 2 O 3 ) / TiO 2 Is less than 0.2.

[0070] In the present invention, 0 to 1% Sb is contained 2 O 3 SnO 2 、CeO 2 One or more components in the glass can be used as a clarifier to improve the clarification effect of the glass and the bubble degree of the glass. The content of the clarifier is preferably 0-0.5%, and more preferably 0-0.1%. Since the component types and contents of the optical glass of the present invention are reasonably designed and the bubble degree is excellent, it is further preferred in some embodiments that no clarifier is contained. When Sb 2 O 3 When the content exceeds 1%, the glass tends to have a reduced clarity performance. At the same time, due to its strong oxidizing effect, it promotes the corrosion of platinum or platinum alloy vessels for melting glass and the deterioration of the molding mold. Therefore, Sb is preferably used in the present invention. 2 O 3 The content of Sb is 0 to 1%, more preferably 0 to 0.5%, further preferably 0 to 0.1%, and further preferably no Sb 2 O 3 SnO 2 It can also be used as a clarifier, but when its content exceeds 1%, the glass tends to be colored more, or when the glass is heated, softened, and molded again, Sn will become the starting point for the formation of crystal nuclei, resulting in a tendency to devitrification. 2 The content of SnO is preferably 0 to 1%, more preferably 0 to 0.5%, further preferably 0 to 0.1%, and further preferably no SnO 2 . CeO2 The role and content ratio of SnO 2 The content is preferably 0 to 1%, more preferably 0 to 0.5%, further preferably 0 to 0.1%, and further preferably CeO is not contained. 2 .

[0071] <Components that should not be contained>

[0072] In the glass of the present invention, even if oxides of transition metals such as V, Cr, Mn, Fe, Co, Ni, Cu, Ag and Mo are contained alone or in combination in small amounts, the glass will be colored and absorption will occur at specific wavelengths in the visible light region, thereby weakening the property of the present invention of improving the visible light transmittance. Therefore, it is preferably substantially free of oxides of transition metals such as V, Cr, Mn, Fe, Co, Ni, Cu, Ag and Mo, especially for optical glasses that require transmittance at wavelengths in the visible light region.

[0073] The oxides of Th, Cd, Tl, Os, Be and Se have a tendency to be controlled in recent years as harmful chemical substances, and environmental protection measures are necessary not only in the manufacturing process of glass, but also in the processing process and the disposal after productization. Therefore, in the case of paying attention to the impact on the environment, it is preferred that they are not actually contained except for being inevitably mixed in. Thus, the optical glass does not actually contain substances that pollute the environment. Therefore, even if special environmental countermeasures are not taken, the optical glass of the present invention can be manufactured, processed and discarded.

[0074] In order to achieve environmental friendliness, the optical glass of the present invention preferably does not contain As 2 O 3 and PbO.

[0075] The "does not contain" and "0%" recorded in this article mean that the compound, molecule or element is not intentionally added as a raw material to the optical glass of the present invention; however, as raw materials and / or equipment for producing optical glass, there will be certain impurities or components that are not intentionally added, which will be contained in a small amount or trace amount in the final optical glass, and this situation is also within the scope of protection of the patent of this invention.

[0076] Next, the properties of the optical glass of the present invention will be described.

[0077] <Refractive Index and Abbe Number>

[0078] The refractive index of optical glass (n d ) and the Abbe number (ν d ) Tested according to the method specified in GB / T 7962.1-2010.

[0079] In some embodiments, the refractive index (n d) has a lower limit of 1.82, a preferred lower limit is 1.83, and a more preferred lower limit is 1.84.

[0080] In some embodiments, the refractive index (n d ) is 1.89, preferably 1.88, and more preferably 1.87.

[0081] In some embodiments, the Abbe number (ν d ) has a lower limit of 18, a preferred lower limit of 20, and a more preferred lower limit of 21.

[0082] In some embodiments, the Abbe number (ν d ) has an upper limit of 26, a preferred upper limit of 25, and a more preferred upper limit of 24.

[0083] <Coefficient of Thermal Expansion>

[0084] Thermal expansion coefficient of optical glass (α 100 / 300℃ ) Test data at 100-300℃ according to the method specified in GB / T7962.16-2010.

[0085] In some embodiments, the thermal expansion coefficient (α 100 / 300℃ ) is 100×10 -7 / K or less, preferably 95×10 -7 / K or less, more preferably 90×10 -7 / K or less.

[0086] <Acid resistance stability>

[0087] Acid resistance stability of optical glass (D A ) (Powder method) Tested in accordance with the method specified in GB / T 17129.

[0088] In some embodiments, the acid resistance stability (D A ) is 2 or more types, preferably 1 type.

[0089] <Water resistance stability>

[0090] Water resistance stability of optical glass (D W ) (Powder method) Tested in accordance with the method specified in GB / T 17129.

[0091] In some embodiments, the water resistance stability (D W ) is 2 or more types, preferably 1 type.

[0092] <Relative partial dispersion and relative partial dispersion deviation value>

[0093] The relative partial dispersion (P g,F ) and relative partial dispersion deviation (ΔP g,F ) origin.

[0094] The relative partial dispersion for wavelengths x and y is expressed by the following equation (1):

[0095] P x,y =(n x -n y ) / (n F -n C ) (1)

[0096] According to the Abbe number formula, for most so-called "normal glasses" (H-K6 and F4 are selected as "normal glasses" below), the following formula (2) is valid:

[0097] P x,y =m x,y ·v d +b x,y (2)

[0098] This linear relationship is based on P x,y is the vertical coordinate, v d It is represented by the horizontal axis, where m x,y is the slope, b x,y is the intercept.

[0099] As is known to all, the correction of the secondary spectrum, i.e. the achromatization of more than two wavelengths, requires at least one glass that does not conform to the above formula (2) (i.e. its P x,y The deviation value deviates from Abbe's empirical formula), and its deviation value is expressed as ΔP x,y If it is expressed, then each P x,y -v d The point is shifted by ΔP relative to the "normal line" that conforms to the above formula (2) x,y Quantity, so that the ΔP of each glass x,y The value can be obtained using the following formula (3):

[0100] P x,y =m x,y ·v d +b x,y +ΔP x,y (3)

[0101] Therefore, ΔP x,y It quantitatively represents the deviation characteristics of special dispersion compared with "normal glass".

[0102] Therefore, the relative partial dispersion (P g,F ) and relative partial dispersion deviation (ΔPg,F ) is calculated as follows (4) and (5):

[0103] P g,F =(n g -n F ) / (n F -n C ) (4)

[0104] ΔP g,F =P g,F -0.6457+0.001703v d (5)

[0105] In some embodiments, the relative partial dispersion (P g,F ) is 0.58 to 0.72, preferably 0.60 to 0.68, and more preferably 0.62 to 0.65.

[0106] In some embodiments, the relative partial dispersion deviation value (ΔP g,F ) is 0.08 or less, preferably 0.005 to 0.06, and more preferably 0.01 to 0.04.

[0107] <Transition Temperature>

[0108] Transition temperature of optical glass (T g ) The test shall be carried out in accordance with the method specified in GB / T7962.16-2010.

[0109] In some embodiments, the transition temperature (T g ) is 670°C or lower, preferably 660°C or lower, and more preferably 650°C or lower.

[0110] <Abrasion>

[0111] Abrasiveness of optical glass (F A ) refers to the value obtained by multiplying the ratio of the wear volume of the sample to the wear volume (volume) of the standard sample (H-K9 glass) under exactly the same conditions by 100, and is expressed by the following formula:

[0112] F A =V / V 0 ×100=(W / ρ) / (W 0 / ρ 0 )×100

[0113] Where: V—volume wear of the sample being tested;

[0114] V 0 —Volume loss of standard sample;

[0115] W—mass wear loss of the sample being tested;

[0116] W 0 —Abrasion loss of standard sample mass;

[0117] ρ—density of the sample being tested;

[0118] ρ 0 —Standard sample density.

[0119] In some embodiments, the abrasiveness (F A ) has a lower limit of 250, a preferred lower limit of 260, and a more preferred lower limit of 265.

[0120] In some embodiments, the abrasiveness (F A ) has an upper limit of 290, a preferred upper limit of 285, and a more preferred upper limit of 280.

[0121] <density>

[0122] The density (ρ) is tested according to the method specified in GB / T7962.20-2010.

[0123] In some embodiments, the density (ρ) of the optical glass of the present invention is 4.00 g / cm 3 Below, preferably 3.90g / cm 3 Below, more preferably 3.80g / cm 3 the following.

[0124] <Color>

[0125] The short-wave transmission spectrum characteristics of the glass of the present invention are expressed by the coloration (λ 70 and λ 5 ) indicates. 70 Refers to the wavelength when the glass transmittance reaches 70%. 70 The measurement is to use a glass with a thickness of 10±0.1mm and two opposite planes parallel to each other and optically polished, and measure the spectral transmittance in the wavelength range from 280nm to 700nm and the wavelength at which the transmittance is 70%. The so-called spectral transmittance or transmittance is the wavelength at which the incident intensity I is perpendicular to the above surface of the glass. in Light of intensity I passes through the glass and emerges from a plane out The light of the case through I out / I in The amount expressed by λ also includes the transmittance of the surface reflection loss on the above surfaces of the glass. The higher the refractive index of the glass, the greater the surface reflection loss. Therefore, in high refractive index glass, λ 70 A small value of means that the glass itself is less colored and has a high light transmittance.

[0126] In some embodiments, the λ of the optical glass of the present invention is 70 430nm or less, preferably λ 70 420nm or less, preferably λ 70 Below 410nm.

[0127] In some embodiments, the λ of the optical glass of the present invention is 5 400nm or less, preferably λ 5 390nm or less, preferably λ 5 Below 380nm.

[0128] <Weather resistance>

[0129] The test method for weather resistance (CR) of optical glass is as follows: place the sample in a test box with a saturated water vapor environment of 90% relative humidity, alternately cycle every 1 hour at 40-50°C, and cycle for 15 cycles. The weather resistance category is divided according to the change in turbidity before and after the sample is placed. The weather resistance classification is shown in Table 1:

[0130] Table 1.

[0131]

[0132] In some embodiments, the weather resistance (CR) of the optical glass of the present invention is Class 2 or higher, preferably Class 1.

[0133] <Young's modulus>

[0134] Young's modulus (E) is calculated using the following formula by ultrasonic testing of its longitudinal wave velocity and transverse wave velocity.

[0135]

[0136] G=V S 2 ρ

[0137] Where: E is Young's modulus, Pa;

[0138] G is the shear modulus, Pa;

[0139] V T is the shear wave velocity, m / s;

[0140] V S is the longitudinal wave velocity, m / s;

[0141] ρ is the glass density, g / cm 3 .

[0142] In some embodiments, the Young's modulus (E) of the optical glass of the present invention is 8000×10 7Pa or more, preferably 8500×10 7 Pa or more, more preferably 9000×10 7 Pa or above.

[0143] <Bubble Degree>

[0144] The bubble degree of optical glass is tested according to the method specified in GB / T7962.8-2010.

[0145] In some embodiments, the bubble degree of the optical glass of the present invention is above grade A, preferably grade A. 0 Grade A or above, preferably A 00 class.

[0146] [Method for producing optical glass]

[0147] The manufacturing method of the optical glass of the present invention is as follows: the glass of the present invention is produced by conventional raw materials and processes, including but not limited to using oxides, hydroxides, complex salts (such as carbonates, nitrates, sulfates, phosphates, metaphosphates, etc.), boric acid, etc. as raw materials, and after mixing according to conventional methods, the prepared furnace materials are put into a melting furnace (such as platinum or platinum alloy crucible) at 1050-1250°C, preferably 1100-1200°C for melting, and after clarification and homogenization, a homogeneous molten glass without bubbles and undissolved substances is obtained, and the molten glass is cast in a mold and annealed. Those skilled in the art can appropriately select raw materials, process methods and process parameters according to actual needs.

[0148] [Glass preforms and optical components]

[0149] The prepared optical glass can be used to make a glass preform by means of direct drop molding, grinding, or compression molding such as hot press molding. That is, the molten optical glass can be directly precision drop molded into a glass precision preform, or the glass preform can be made by mechanical processing such as grinding and grinding, or the preform for compression molding made of the optical glass can be made by hot press molding and then grinding. It should be noted that the means for preparing the glass preform are not limited to the above means.

[0150] As described above, the optical glass of the present invention is useful for various optical elements and optical designs, and it is particularly preferred to form a preform from the optical glass of the present invention and use the preform to perform re-hot pressing, precision stamping, etc. to produce optical elements such as lenses and prisms.

[0151] The glass preform and optical element of the present invention are both formed of the optical glass of the present invention. The glass preform of the present invention has the excellent properties of optical glass; the optical element of the present invention has the excellent properties of optical glass, and can provide various optical elements such as lenses and prisms with high optical value.

[0152] Examples of the lens include various lenses having spherical or aspherical lens surfaces, such as a concave meniscus lens, a convex meniscus lens, a biconvex lens, a biconcave lens, a plano-convex lens, and a plano-concave lens.

[0153] [Optical instruments]

[0154] The optical element formed by the optical glass of the present invention can be used to manufacture optical instruments such as photographic equipment, video equipment, projection equipment, display equipment, vehicle-mounted equipment and monitoring equipment.

[0155] Example

[0156] <Optical Glass Example>

[0157] In order to further clearly illustrate and describe the technical solution of the present invention, the following non-limiting examples are provided.

[0158] This embodiment adopts the above optical glass manufacturing method to obtain optical glasses having the compositions shown in Tables 2 to 4. In addition, the properties of each glass are measured by the testing method described in the present invention, and the measurement results are shown in Tables 2 to 4.

[0159] Table 2.

[0160]

[0161]

[0162]

[0163] Table 3.

[0164]

[0165]

[0166] Table 4.

[0167]

[0168]

[0169]

[0170] <Glass Preform Example>

[0171] The glass obtained from optical glass examples 1 to 21# is used, for example, by grinding processing, or by molding methods such as hot pressing, precision stamping, etc., to make preforms of various lenses, prisms, etc., such as concave meniscus lenses, convex meniscus lenses, biconvex lenses, biconcave lenses, plano-convex lenses, and plano-concave lenses.

[0172] <Optical Element Embodiment>

[0173] The preforms obtained in the above-mentioned glass preform embodiments are annealed to reduce the internal stress of the glass and fine-tune the refractive index so that the optical properties such as the refractive index reach the desired values.

[0174] Next, each preform is ground and polished to produce various lenses and prisms such as concave meniscus lenses, convex meniscus lenses, biconvex lenses, biconcave lenses, plano-convex lenses, and plano-concave lenses. The surface of the obtained optical element may be coated with an anti-reflection film.

[0175] <Optical Instrument Embodiment>

[0176] The optical element obtained by the above-mentioned optical element embodiment is optically designed to form an optical component or optical assembly by using one or more optical elements, and can be used in, for example, imaging equipment, sensors, microscopes, medical technology, digital projection, communications, optical communication technology / information transmission, optics / lighting in the automotive field, lithography technology, excimer lasers, wafers, computer chips, and integrated circuits and electronic devices including such circuits and chips.

Claims

1. Optical glass, characterized in that: Its components, expressed in weight percentage, include: P2O5: 20-35%; Nb2O5: 37-55%; TiO2: 1-12%; BaO: 4-19%; Na2O: 0.5-14%.

2. The optical glass according to claim 1, characterized in that: Its components, expressed in weight percentage, also contain: CaO: 0-8%; and / or MgO: 0-5%; and / or SrO: 0-8%; and / or ZnO: 0-5%; and / or Li2O: 0-5%; and / or K2O: 0-5%; and / or Ln2O3: 0-5%; and / or SiO2: 0-5%; and / or B2O3: 0-5%; and / or Al2O3: 0-3%; and / or WO3: 0-3%; and / or ZrO2: 0-5%; and / or Bi2O3: 0-3%; and / or clarifier: 0-1%, wherein the Ln2O3 is one or more of La2O3, Gd2O3, Y2O3, Yb2O3, and Lu2O3, and the clarifier is one or more of Sb2O3, SnO2, and CeO2.

3. Optical glass, characterized in that: Its components, expressed in weight percentage, are P2O5: 20-35%; Nb2O5: 37-55%; TiO2: 1-12%; BaO: 4-19%; Na2O: 0.5-14%; CaO: 0-8%; MgO: 0-5%; SrO: 0-8%; The invention comprises the following components: ZnO: 0-5%; Li2O: 0-5%; K2O: 0-5%; Ln2O3: 0-5%; SiO2: 0-5%; B2O3: 0-5%; Al2O3: 0-3%; WO3: 0-3%; ZrO2: 0-5%; Bi2O3: 0-3%; and clarifier: 0-1%, wherein Ln2O3 is one or more of La2O3, Gd2O3, Y2O3, Yb2O3 and Lu2O3, and the clarifier is one or more of Sb2O3, SnO2 and CeO2.

4. The optical glass according to any one of claims 1 to 3, characterized in that: Its components are expressed in weight percentage, wherein: (ZnO+Li2O+K2O+WO3+B2O3+Bi2O3) / SrO is less than 2.0, preferably (ZnO+Li2O+K2O+WO3+B2O3+Bi2O3) / SrO is less than 1.5, and more preferably (ZnO+Li2O+K2O+WO3+B2O3+Bi2O3) / SrO is less than 1.0, and more preferably (ZnO+Li2O+K2O+WO3+B2O3+Bi2O3) / SrO is less than 0.

5.

5. The optical glass according to any one of claims 1 to 3, characterized in that: in: (Li2O+B2O3+Bi2O3) / TiO2 is less than 1.0, preferably (Li2O+B2O3+Bi2O3) / TiO2 is less than 0.8, more preferably (Li2O+B2O3+Bi2O3) / TiO2 is less than 0.5, and further preferably (Li2O+B2O3+Bi2O3) / TiO2 is less than 0.

2.

6. The optical glass according to any one of claims 1 to 3, characterized in that: Its components are expressed in weight percentage, wherein: SrO / TiO2 is 0.01-5.0, preferably SrO / TiO2 is 0.01-2.0, more preferably SrO / TiO2 is 0.05-1.0, and further preferably SrO / TiO2 is 0.1-0.

7.

7. The optical glass according to any one of claims 1 to 3, characterized in that: The composition is expressed in weight percentage, wherein: BaO / (Na2O+K2O+TiO2) is 0.4-5.0, preferably BaO / (Na2O+K2O+TiO2) is 0.5-3.0, more preferably BaO / (Na2O+K2O+TiO2) is 0.6-2.5, and further preferably BaO / (Na2O+K2O+TiO2) is 0.7~1.

5.

8. The optical glass according to any one of claims 1 to 3, characterized in that: Its components are expressed in weight percentage, wherein: Nb2O5 / P2O5 is 1.3-2.7, preferably Nb2O5 / P2O5 is 1.4-2.5, more preferably Nb2O5 / P2O5 is 1.5-2.2, and further preferably Nb2O5 / P2O5 is 1.6-2.

0.

9. The optical glass according to any one of claims 1 to 3, characterized in that: Its components are expressed in weight percentage, wherein: (SiO2+CaO+ZnO) / SrO is 0.3~8.0, preferably (SiO2+CaO+ZnO) / SrO is 0.5~5.0, more preferably (SiO2+CaO+ZnO) / SrO is 0.6~3.0, and further preferably (SiO2+CaO+ZnO) / SrO is 0.7~2.

0.

10. The optical glass according to any one of claims 1 to 3, characterized in that: Its components are expressed in weight percentage, wherein: (WO3+ZnO+K2O+CaO+MgO) / TiO2 is less than 2.0, preferably (WO3+ZnO+K2O+CaO+MgO) / TiO2 is 0.05~1.5, more preferably (WO3+ZnO+K2O+CaO+MgO) / TiO2 is 0.1~1.0, and further preferably (WO3+ZnO+K2O+CaO+MgO) / TiO2 is 0.2~0.

8.

11. The optical glass according to any one of claims 1 to 3, characterized in that: Its components are expressed in weight percentage, wherein: (WO3+K2O+TiO2+B2O3) / Nb2O5 is 0.03-0.4, preferably (WO3+K2O+TiO2+B2O3) / Nb2O5 is 0.04-0.3, more preferably (WO3+K2O+TiO2+B2O3) / Nb2O5 is 0.05-0.25, and further preferably (WO3+K2O+TiO2+B2O3) / Nb2O5 is 0.06-0.

15.

12. The optical glass according to any one of claims 1 to 3, characterized in that: The components are expressed in weight percentage, wherein: Na2O / BaO is 0.05-2.0, preferably Na2O / BaO is 0.1-1.5, more preferably Na2O / BaO is 0.2-1.0, and further preferably Na2O / BaO is 0.4-0.

9.

13. The optical glass according to any one of claims 1 to 3, characterized in that: Its components are expressed in weight percentage, wherein: BaO / P2O5 is 0.15-0.9, preferably BaO / P2O5 is 0.25-0.8, more preferably BaO / P2O5 is 0.3-0.7, and further preferably BaO / P2O5 is 0.35-0.

6.

14. The optical glass according to any one of claims 1 to 3, characterized in that: Its components are expressed in weight percentage, wherein: (Li2O+B2O3+TiO2) / BaO is 0.06-2.0, preferably (Li2O+B2O3+TiO2) / BaO is 0.07-1.5, more preferably (Li2O+B2O3+TiO2) / BaO is 0.08-1.0, and further preferably (Li2O+B2O3+TiO2) / BaO is 0.1-0.

5.

15. The optical glass according to any one of claims 1 to 3, characterized in that: Its components are expressed in weight percentage, wherein: TiO2 / CaO is 0.4-10.0, preferably TiO2 / CaO is 0.8-8.0, more preferably TiO2 / CaO is 1.0-6.0, and further preferably TiO2 / CaO is 1.2-5.

0.

16. The optical glass according to any one of claims 1 to 3, characterized in that: Its components are expressed in weight percentage, wherein: P2O5: 22-32%, preferably P2O5: 25-30%; and / or Nb2O5: 41-52%, preferably Nb2O5: 43-50%; and / or TiO2: 2-10%, preferably TiO2: 3-7%; and / or BaO: 6-16.5%, preferably BaO: 10-15%; and / or Na2O: 2-12%, preferably Na2O : 5-10%; and / or CaO: greater than 0 but less than or equal to 6%, preferably CaO: 1-4%; and / or MgO: 0-3%, preferably MgO: 0-1%; and / or SrO: greater than 0 but less than or equal to 5%, preferably SrO: 0.5-3%; and / or ZnO: 0-3%, preferably ZnO: 0-1%; and / or Li2O: 0-3%, preferably Li2O: 0-1%; and / or K2O: 0-3%, preferably K2O: 0-1%; and / or Ln2O3: 0-3%, preferably Ln2O3: 0-1%; and / or SiO2: 0-3%, preferably SiO2: 0-1%; and / or B2O3: 0-3%, preferably B2O3: 0-1%; and / or Al2O3: 0-2%, preferably Al2O3: 0-1%; and / or WO3: 0-2%, preferably WO3: 0-1%; and / or ZrO2: 0-2%, preferably ZrO2: 0-1%; and / or Bi2O3: 0-2%, preferably Bi2O3: 0-1%; and / or clarifier: 0-0.5%, preferably clarifier: 0-0.1%, the Ln2O3 is one or more of La2O3, Gd2O3, Y2O3, Yb2O3, Lu2O3, and the clarifier is one or more of Sb2O3, SnO2, CeO2.

17. The optical glass according to any one of claims 1 to 3, characterized in that: Its components do not contain MgO; and / or do not contain ZnO; and / or do not contain Li2O; and / or do not contain K2O; and / or do not contain Ln2O3; and / or do not contain B2O3; and / or do not contain Al2O3; and / or do not contain WO3; and / or do not contain ZrO2; and / or do not contain Bi2O3; and / or do not contain clarifiers, and the Ln2O3 is one or more of La2O3, Gd2O3, Y2O3, Yb2O3, and Lu2O3, and the clarifier is one or more of Sb2O3, SnO2, and CeO2.

18. The optical glass according to any one of claims 1 to 3, characterized in that: The refractive index n of the optical glass d 1.82 to 1.89, preferably 1.83 to 1.88, more preferably 1.84 to 1.87; Abbe number ν d It is 18-26, preferably 20-25, and more preferably 21-24.

19. The optical glass according to any one of claims 1 to 3, characterized in that: The thermal expansion coefficient of the optical glass is α 100 / 300℃ 100×10 -7 / K or less, preferably 95×10 -7 / K or less, more preferably 90×10 -7 / K or less; and / or acid resistance stability D A 2 or more, preferably 1; and / or water resistance stability D W Two or more types, preferably one type; and / or relative partial dispersion P g,F 0.58 to 0.72, preferably 0.60 to 0.68, more preferably 0.62 to 0.65; and / or relative partial dispersion deviation value ΔP g,F is 0.08 or less, preferably 0.005 to 0.06, more preferably 0.01 to 0.04; and / or the transition temperature T g 670°C or less, preferably 660°C or less, more preferably 650°C or less; and / or abrasion degree F A 250 to 290, preferably 260 to 285, more preferably 265 to 280; and / or density ρ is 4.00 g / cm 3 Below, preferably 3.90g / cm 3 Below, more preferably 3.80g / cm 3 Below; and / or 70 430nm or less, preferably λ 70 420nm or less, preferably λ 70 is 410nm or less; and / or λ5 is 400nm or less, preferably λ5 is 390nm or less, more preferably λ5 is 380nm or less; and / or weather resistance CR is 2 or more, preferably 1; and / or Young's modulus E is 8000×10 7 Pa or more, preferably 8500×10 7 Pa or more, more preferably 9000×10 7 Pa or more; and / or the bubble degree is A grade or more, preferably A0 grade or more, more preferably A 00 class.

20. A glass preform, characterized in that: Made of the optical glass described in any one of claims 1 to 19.

21. An optical element, characterized in that The optical glass is made of any one of claims 1 to 19, or the glass preform is made of claim 20.

22. An optical instrument, characterized in that A method of manufacturing an optical device comprising the optical glass according to any one of claims 1 to 19, or comprising the optical element according to claim 21.

Citation Information

Patent Citations

  • Optical glass

    CN101289275A

  • Optical glass

    CN101932532A

  • Optical glass

    CN102471130A

  • Optical glass

    CN1186279C

  • Optical glass

    CN1229293C